Cognitive appraisals and team performance under stress: A simulation study. Issue 3 (7th February 2020) - Carenzo, Luca; Braithwaite, Elizabeth C.; Carfagna, Fabio; Franc, Jeffrey; Ingrassia, Pier Luigi; Turner, Martin J.; Slater, Matthew J.; Jones, Marc V.
Abstract: Objectives: The present study explored how challenge and threat responses to stress relate to performance, anxiety, confidence, team identity and team characteristics (time spent in training and postgraduate experience) in a medical simulation‐based team competition. Methods: The study was conducted during a national simulation‐based training event for residents, the SIMCUP Italia 2018. The SIMCUP is a simulation competition in which teams of four compete in simulated medical emergency scenarios. Cross‐sectional data were collected prior to the 3 days of the competition. Subjects included 95 participants on 24 teams. Before the competition on each day, participants completed brief self‐report measures that assessed demands and resources (which underpin challenge and threat responses to stress), cognitive and somatic anxiety, self‐confidence and team identification. Participants also reported time (hours) spent practising as a team and years of postgraduate experience. A team of referees judged each scenario for performance and assigned a score. A linear mixed model using demands and resources was built to model performance. Results: The data showed that both demands and resources have positive effects on performance (31 [11‐50.3] [ P < .01] and 54 [25‐83.3] [ P < .01] percentage points increase for unitary increases in demands and resources, respectively); however, this is balanced by a negative interaction between the two (demands * resources interaction coefficient = −10 [−16 to −4.2]). A high level of resources is associated with better performance until demands become very high. Cognitive and somatic anxieties were found to be correlated with demands (Pearson's r = .51 [ P < .01] and Pearson's r = .48 [ P < .01], respectively). Time spent training was associated with greater perceptions of resources (Pearson's r = .36 [ P < .01]). Conclusions: We describe a model of challenge and threat that allows for the estimation of performance according to perceived demands and resources, and the interaction between the two. Higher levels of resources and lower demands were associated with better performance. Abstract : How do challenge and threat responses to stress impact performance, confidence, and team identity? These factors along with others are explored in this study in the context of a medical simulation competition.